Anteseden Kinerja Karyawan PT. Bank Mandiri Persero Tbk Area Jakarta Cikini - Doddy Pratama; Medina Nilasari (ijd-demos, 2022)
AbstractThe problem of this research comes from a phenomenon that occurred to employees in PT. Bank Mandiri (Persero) Tbk Area Jakarta Cikini. The objectives of the research are to analyze: (1) whether Internal Branding has effect on Affective Commitment; (2) whether Affective Commitment has effect on Employee Engagement; (3) whether Affective Commitment has effect on Job Satisfaction; (4) whether Employee Engagement has effect on Job Performance; (5) whether Job Satisfaction has effect on Job Performance; (6) whether Internal Branding has effect on Job Satisfaction. The research took sample from 124 (one hundred and twenty-four) employee of PT. Bank Mandiri (Persero) Tbk Area Jakarta Cikini and the number of samples represents the existing population. Validity and reliability are used to test the research instruments. The methodology of this research uses cross-sectional data and hypothesis testing. Data was collected by using questionnaires and the measurement scale was using Likert scale. The  results of this research indicate that: (1) Internal Branding has positive effect on Affective Commitment; (2) Affective Commitment not positive effect on Employee Engagament; (3) Affective Commitment not positive effect on Job Satisfaction; (4) Employee Engagement has positive effect on Job Performance; (5) Job Satisfaction has positive effect to Job Performance; (6) Internal Branding has positive effect on Employee Engagement; (7) Internal Branding has positive effect on Job Satisfaction. This research only analyzed five variables job performance, employee engagement, job satisfaction, internal branding and affective commitment. Futher research is required to analyze the effect of other variables by using construct in this research.Keywords: Job Performance, Employee Engagement, Job Satisfaction, Internal Branding, Affective Commitment. AbstrakMasalah penelitian ini berangkat dari sebuah fenomena yang terjadi pada karyawan di PT. Bank Mandiri (Persero) Tbk Area Jakarta Cikini. Penelitian ini bertujuan untuk menganalisis:(1) Apakah Internal Branding berpengaruh terhadap Affective Commitment; (2) Apakah Affective Commitment berpengaruh terhadap Employee Engagement; (3) Apakah Affective Commitment berpengaruh terhadap Job Satisfaction; (4) Apakah Employee Engagement berpengaruh terhadap Job Performance; (5) Apakah Job Satisfaction berpengaruh terhadap Job Performance; (6) Apakah Internal Branding berpengaruh terhadap Job Satisfaction.Penelitian ini mengambil sampel dari 124 (seratus dua puluh empat) karyawan PT. Bank Mandiri (Persero) Tbk Area Jakarta Cikini dan jumlah sampel mewakili populasi yang ada. Validitas dan reliabilitas digunakan untuk menguji instrumen penelitian. Metodologi penelitian ini menggunakan data cross-sectional dan pengujian hipotesis. Pengumpulan data menggunakan kuesioner dan skala pengukuran menggunakan skala Likert. Hasil penelitian ini menunjukkan bahwa: (1) Internal Branding berpengaruh positif terhadap Affective Commitment; (2) Affective Commitment tidak berpengaruh positif terhadap Employee Engagament; (3) Affective Commitment tidak berpengaruh positif terhadap Job Satisfaction; (4) Employee Engagement berpengaruh positif terhadap Job Performance; (5) Job Satisfaction berpengaruh positif terhadap Job Performance; (6) Internal Branding berpengaruh positif terhadap Employee Engagement; (7) Internal Branding berpengaruh positif terhadap Job Satisfaction.Penelitian ini hanya menganalisis lima variabel job performance, employee engagement, job satisfaction, internal branding dan affective commitment. Diperlukan penelitian lebih lanjut untuk menganalisis pengaruh variabel lain dengan menggunakan konstruk dalam penelitian ini.Kata Kunci: Prestasi Kerja, Keterlibatan Karyawan, Kepuasan Kerja, Branding Internal, Komitmen Afektif.